Positive experiences of distance education from the perspective of primary school pupils, grades I–III - Agnieszka Koterwas; Edyta Nowosielska (Problemy Wczesnej Edukacji)
The article refers to a broader research project on how the COVID-19 pandemic affected everyday school life during distance education in grades I–III of primary school. The empirical data collected in 2021 were based on focus interviews with pupils in six primary schools. In our quantitative analysis of the data, we concentrated on the pupils whose experiences of distance learning during the pandemic were perceived – by the pupils – as positive. These experiences were primarily the effect of students being in a comfortable home and virtual space. In both spaces, compared to education within the walls of a school, firstly, students had a wider range of different activities possible to undertake, and secondly, the teacher’s directive nature in the learning process was limited. As a result, conditions were created for the formation of student agency and autonomy, while at the same time posing as learning, hiding from the teacher, or “pretending” to fulfill school duties.